Partnering with Palliative Care: A Case Report of Severe Pain in Critical Limb Ischemia Treated Successfully with a Continuous Popliteal Nerve Catheter - Ryan S. D’Souza; Stephanie Shen; Frederick Ojukwu; Halena M. Gazelka; Bridget P. Pulos (Case Reports in Anesthesiology)
Background. Critical limb ischemia (CLI) is limb pain occurring at rest or impending limb loss as a result of lack of blood flow to the affected extremity. CLI pain is challenging to control despite multimodal pharmacologic analgesia and surgical intervention. We described the successful use of a continuous local anesthetic infusion via a popliteal nerve catheter to control severe refractory ischemic lower limb pain in a patient who failed surgical intervention and performed a brief narrative literature review on regional anesthesia for ischemic pain. Case Presentation. A 74-year-old female with acute myelogenous leukemia presented with CLI after experiencing left popliteal artery occlusion. Palliative medicine service was consulted for pain management in the setting of escalating narcotic dose requirements. She experienced a complicated hospital course with several failed attempts at surgical revascularization due to arterial rethrombosis. In accordance with the patient’s goals of care, a continuous popliteal nerve catheter was placed, despite the high risk nature of an intervention in an immunocompromised patient with thrombocytopenia (platelet count of 30,000 platelets/microliter) and ongoing therapeutic anticoagulation. The patient experienced immediate relief while transitioning to comfort care. Conclusion. This is the first report of successful analgesia for CLI via a continuous popliteal catheter in a patient with rethrombosis and failed surgical revascularization. Based on our collaborative experience, we recommend the development of partnerships between the acute pain service and palliative care service to facilitate the early evaluation and decision to utilize regional anesthesia for treatment of CLI.